Severe community-acquired pneumonia: current management and future therapeutic alternatives. Issue 9 (2nd September 2018) - Garnacho-Montero, Jose; Barrero-García, Irene; Gómez-Prieto, Maria de Gracia; Martín-Loeches, Ignacio
ABSTRACT: Introduction : Despite advances in modern medicine, severe community-acquired pneumonia (CAP) continues to be a potentially deadly disease. Mortality rate reaches up to the 50% in patients requiring admission to the Intensive Care Unit (ICU) when developing septic shock. Areas covered : We aim to describe the optimal management of severe CAP, including antibiotic therapy, future antimicrobial options, and non-antibiotic (so-called adjunctive) therapies. A literature search was performed to identify all clinical trials, observational studies, meta-analysis, and reviews about this topic from PubMed. Expert commentary : Antibiotic therapy, the cornerstone of the management of CAP, must be started prompt because the delay in the administration of antimicrobials is associated with mortality. Diverse observational studies have reported a lower adjusted mortality in patients with severe CAP treated with combined antibiotic therapy, especially those in septic shock or with pneumococcal bacteremia. We summarize the available information about new antibiotics in the pipeline for severe CAP. Finally, we review the available evidence about the role of corticosteroids, immunoglobulins, and statins as adjunctive for CAP.